An illustrated manual for environmental DNA research: Water sampling guidelines and experimental protocols - Toshifumi Minamoto; Masaki Miya; Tetsuya Sado; Satoquo Seino; Hideyuki Doi; Michio Kondoh; Keigo Nakamura; Teruhiko Takahara; Satoshi Yamamoto; Hiroki Yamanaka; Hitoshi Araki; Wataru Iwasaki; et al. (Environmental DNA, 2021)
Abstract Environmental DNA (eDNA)‐based assessments of macro‐organisms have now become an essential approach for biomonitoring. eDNA survey methods have a number of advantages over conventional survey methods. However, the value of the data that will accumulate would be greatly enhanced by standardizing the analysis methods, which would allow us to compare data from multiple monitoring sites at different points in time. The eDNA Society (http://ednasociety.org/en/about), whose founding members consist of Japanese researchers conducting eDNA studies on macro‐organisms, was established in 2018, with the aim of expanding eDNA technology and science. Here, we introduce our key publication, “Environmental DNA Sampling and Experiment Manual” (http://ednasociety.org/en/manual), which was published under the initiative of the eDNA Society. Detailed methods for the surveys and experiments are described in the manual, including the selection of sampling sites, sampling methods, filtration methods, DNA extraction, species‐specific detection by real‐time polymerase chain reaction, and fish eDNA metabarcoding. The manual assists users in conducting standardized surveys and quality experiments, and provides a basis for collecting comparable data. Given that the efficacy of methods can be context dependent and variable, and that procedures may sometimes conflict with standardization, it is difficult to ensure that all processes are equally effective. However, even in such cases, it is important to maintain sufficiently high data quality by setting the minimum standards to be followed. Implementation of such standardized methodologies will enable the systematic and frequent collection of flawless, comparable eDNA data from around the world; this will provide important fundamental information for biodiversity conservation, as well as the sustainable use of fisheries resources.